A new method for estimation of aerostatic stability safety factors of cable-stayed bridges. Issue 1 (9th February 2018) - Dong, Fenghui; Cheng, Jin
Abstract : An inverse reliability-based approach is proposed to estimate the aerostatic stability safety factors of long-span cable-stayed bridges in order that their reliability against the failure mode of aerostatic stability meets a desired level of safety. For the purpose of estimation, uncertainties associated with the basic wind speed at the bridge deck location, critical aerostatic stability velocity, the wind conversion factor from a scaled model to the prototype structure and the gust speed factor are taken into account. The proposed approach combines concepts from the inverse reliability method and the calculation method of the critical aerostatic stability velocity of long-span cable-stayed bridges. A procedure of the proposed approach for the estimation of aerostatic stability safety factor, which at the same time achieves a target reliability, is outlined. This proposed approach is illustrated using three existing long-span cable-stayed bridges. The results indicate that the proposed approach provides validity information concerning the improved accuracy of the estimation of aerostatic stability of long-span cable-stayed bridges over the traditional method. Additionally, the effects of various parameters on the aerostatic stability safety factor of long-span cable-stayed bridges are analysed and discussed.